Implementasi Good Corporate Governance, Budaya Organisasi dan Kinerja Manajerial pada Hotel Berbintang di Kabupaten Badung - Hilldayani, Ni Wayan Prita Wanda; Putri, I Gusti Ayu Made Asri Dwija; Mimba, Ni Putu Sri Harta; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2021)
Performance is the result of work that can be achieved by a person or group in the company in accordance with the authority and responsibility in an effort to achieve company goals. Badung Regency has the most number of star-rated hotels in Bali. Many factors can affect performance including Good Corporate governance (GCG) and organizational culture. The research objective is to determine the effect of GCG principles and organizational culture on managerial performance. The study was conducted in 61 star hotels in Badung Regency. The data analysis technique used is multiple linear regression analysis. This study shows the results that the variable Independence and Organizational Culture has a positive effect on managerial performance, while the variables Transparency, Accountability, Responsibility and Fairness do not affect managerial performance. Keywords: Managerial Performance; Good Corporate Governance; Organizational Culture.